THE STRUCTURAL-SEMANTIC CLASSIFICATION OF AFFIXAL MORPHEMES IN THE UZBEK LANGUAGE (The Conference Hub, 2025)
This article provides a comprehensive examination of the structural and semantic classification of affixal morphemes in the Uzbek language, emphasizing its agglutinative morphological system. It explores how affixal morphemes—particularly suffixes, prefixes, interfixes, infixes, and circumfixes—function in modifying the grammatical and lexical properties of root words. Structurally, the paper outlines the positional behavior of affixes and their role in recursive morphological construction, while semantically it distinguishes between inflectional, derivational, and formative functions. The interaction between structure and meaning is analyzed to show how affixes contribute to the language’s expressive potential. The study also highlights phonological phenomena such as vowel harmony and morphotactic sequencing, which further illustrate the cohesive integration of affixes in Uzbek word formation. This analysis contributes to the understanding of Uzbek morphology and offers insights relevant to language learning, linguistic theory, and computational processing.